2002
DOI: 10.1007/s00438-002-0744-8
|View full text |Cite
|
Sign up to set email alerts
|

clap1, a gene encoding a copper-transporting ATPase involved in the process of infection by the phytopathogenic fungus Colletotrichum lindemuthianum

Abstract: A screen for insertional mutants of Colletrichum lindemuthianum, the causative agent of common bean anthracnose, led to the identification of a non-pathogenic, lightly colored transformant. This mutant is unable to induce disease symptoms on intact or wounded primary leaves of seedlings and plantlets of Phaseolus vulgaris. In vitro, it exhibits normal vegetative growth, sporulation and conidial germination, but the cultures remain beige instead of becoming black. Microscopic examination revealed that this muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 46 publications
(64 reference statements)
6
48
0
Order By: Relevance
“…In the present study, we identified two putative secreted laccases that differed in amino acid sequence (data not shown), suggesting that C. higginsianum deploys at least two laccase isoenzymes. We also found a homologue of the copper-transporting ATPase CLAP1, which is required for appressorial melanization in C. lindemuthianum and is thought to deliver copper to secreted cuproenzymes such as laccases (Parisot et al, 2002).…”
Section: Putative Virulence and Pathogenicity Genesmentioning
confidence: 77%
“…In the present study, we identified two putative secreted laccases that differed in amino acid sequence (data not shown), suggesting that C. higginsianum deploys at least two laccase isoenzymes. We also found a homologue of the copper-transporting ATPase CLAP1, which is required for appressorial melanization in C. lindemuthianum and is thought to deliver copper to secreted cuproenzymes such as laccases (Parisot et al, 2002).…”
Section: Putative Virulence and Pathogenicity Genesmentioning
confidence: 77%
“…Although many studies have shown that the Cu detoxification system plays important roles in virulence of human pathogens [15,48,49], to date there hasn’t been a study of a role for CrpA in a plant pathogenic fungus, nor is there any evidence the plant cells use Cu as a defense mechanism. The only study investigating any role of a Cu transporter in a plant pathogen is where a Cu golgi transporter, BcCCC2, in the pathogen Botrytis cinerea was found important for virulence in that fungus [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the fungal pathogen C. neoformans, activity of the melanin biosynthetic enzyme laccase, which is required for virulence (30), is influenced by copper levels (42). Other data imply a more direct role for copper transporters during infection of the host; for example, clap1, the ortholog of H. capsulatum CRP1 in the phytopathogenic fungus C. lindemuthianum, is required for pathogenesis (25). Similarly, mutation of CtpA, a coppertransporting P-type ATPase in Listeria monocytogenes, results in a marked reduction in host colonization (9).…”
Section: Discussionmentioning
confidence: 99%